The proteasome maturation protein POMP increases proteasome assembly and activity in psoriatic lesional skin. Issue 1 (October 2017) - Zieba, Barbara A.; Henry, Laurent; Lacroix, Matthieu; Jemaà, Mohamed; Lavabre-Bertrand, Thierry; Meunier, Laurent; Coux, Olivier; Stoebner, Pierre-Emmanuel
Highlights: The main proteasome forms are enhanced in psoriatic lesional skin. POMP increases proteasome assembly in psoriatic skin. POMP silencing impairs keratinocyte viability and delays keratinocyte differentiation. Abstract: Background: The ubiquitin proteasome pathway is involved in the pathogenesis of psoriasis and proteasome subunits are increased in lesional psoriatic skin. Recent works have highlighted that proteasome levels can be regulated through modulation of proteasome assembly notably by the proteasome maturation protein POMP. Objectives: To investigate whether proteasome assembly and POMP expression are modified in psoriatic skin. Methods: Proteasome assembly as well as expression of proteasome regulators were assessed in non-lesional and lesional psoriatic skin using native gel electrophoresis and western blots respectively. The protein and mRNA expression levels of POMP were compared by western blots, immunohistochemistry and quantitative polymerase chain reaction. The role of POMP in keratinocyte proliferation and differentiation was assessed by silencing POMP gene expression by RNA interference in human immortalized keratinocyte HaCaT cells. Results: Both 20S and 26S proteasomes (and their respective proteolytic activities) as well as the main proteasome regulators are increased in lesional psoriatic skin. POMP binds to 20S precursor complexes and is overexpressed in lesional epidermal psoriatic skin, supporting that POMP-mediated proteasome assembly is increased in psoriatic skin. POMP silencing inhibited HaCaT cell proliferation and induced apoptosis through the inhibition of the proteasome assembly. Moreover POMP partial depletion decreased the expression of the differentiation markers keratin 10 and involucrin during the [Ca 2+ ]-induced HaCaT cells differentiation. Conclusion: Altogether these results establish a potential role for POMP and proteasome assembly in psoriasis pathogenesis.